A Note on Three Classes of Nonlinear Parabolic Equations with Measurable Coefficients (Journal of Partial Differential Equations, 2020)
In this note a note and simple technique is presented to replace the complicated one in [1] to obtain Hölder continuity of the weak solutions for a class of nonlinear parabolic equations with measurable coefficients, whose prototype is the singular p-Laplacian. This new approach is also applied to two other classes of nonlinear parabolic equations with measurable coefficients, whose weak solutions exhibit the similar property to those of equations mentioned above.
Keywords: Hölder continuity; nonlinear parabolic equations measurable coefficients